Policy Output Analysis dalam Penanganan Perempuan Korban Kekerasan di DP2KBP3A Kabupaten Kediri - Muhamad Wahyu Rahmasaputra; Arimurti Kriswibowo (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
Violence against women is a serious public problem and requires effective and efficient handling. This study aims to analyze the policy output analysis in handling women victims of violence in DP2KBP3A, Kediri Regency. One of the Regional Apparatus Organizations (OPD) that oversees the handling of women victims of violence in Kediri Regency is DP2KBP3A Kediri Regency. This study uses a qualitative descriptive approach, this research finds that the output of policies in handling women victims of violence in DP2KBP3A Kediri Regency has been effective in achieving its goals, because in evaluating program outputs, namely access, coverage, frequency, bias, service accuracy, accountability and the suitability of the program with the needs has been effective in its implementation. However, DP2KBP3A Kediri Regency still has obstacles, namely the lack of human resources, especially in financial management and the absence of a safe house shelter (House Protection) for handling women victims of violence.